RELATIONSHIP BETWEEN STRESS LEVEL AND EMOTIONAL EATING WITH NUTRITIONAL STATUS IN HEALTH FACULTY STUDENTS AT MUHAMMADIYAH GRESIK UNIVERSITY - Syafiqah, Talitha Safa; Ariestiningsih, Eka Srirahayu; Supriatiningrum, Dwi Novri (Ghidza Media Jurnal, 2024)
This study found that when a person experiences stress, it will cause a response in the form of emotional eating. Emotional eating is an eating urge that arises in response to negative emotions. This study aims to determine the relationship between stress levels, emotional eating and nutritional status in students of Universitas Muhammadiyah Gresik Faculty of Health. This research was conducted on 81 students of level I, II and III. The measuring instruments used in this study used the Perceived Sources Academy of Stress, the Dutch Eating Behavior Questionnaire (DEBQ) scale, anthropometric data and 2x24 hour Recall. Bivariate analysis was performed using the Spearman Rank test and multivariate analysis using multiple linear regression. Results: 93.8% of respondents experienced severe stress levels, 45.7% of respondents experienced moderate emotional eating and 61.7% of respondents had normal nutritional status. There is a significant relationship between stress levels and emotional eating (Sig. of 0.001 (0.001 <0.05) and there is no significant relationship between stress levels, emotional eating and nutritional status (p = 0.700; p = 0.876). So, it can be concluded that respondents should be able to manage stress well and maintain the intake of food to be consumed.